(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article tells about the history of the creation and development of the first museums of Uzbekistan, the formation of the first exhibitions, the architecture and interiors of museum buildings of the former Soviet Union and the first years of independence.